Silymarin as a phytopharmaceutical agent: advances in mechanistic insights, formulation strategies, and pre-clinical applications - Sayyad, Mahewish; Sutar, Ashish Dilip; Shivhare, Kamini; Shukla, Rahul; Flora, Swaran J. S. (Frontiers in Pharmacology, 2025)
Silymarin, extracted from the seeds of Silybum marianum (milk thistle), has been utilised in traditional medicine for many years and is recognised for its neuroprotective and hepatoprotective properties. Existing research reveals that silymarin has potent antioxidant and anti-inflammatory effects, coupled with anti-fibrotic, anti-carcinogenic, neuro-regenerative, and immunomodulatory actions, and has broad therapeutic relevance in both neurological and hepatic disorders, albeit with the drawback of low solubility. Silymarin participates in multiple molecular and cellular pathways to show its therapeutic effect. Nanocarriers are a promising solution to silymarin’s low solubility and limited bioavailability, aiming to enhance targeted delivery to the central nervous system and hepatic tissue. These developments position silymarin as a multi-domain phytopharmaceutical with significant translational potential. This review provides an overview of silymarin’s historical context, phytochemical composition, and pharmacokinetic profile, with a particular focus on targeted drug delivery systems. Special emphasis is placed on its potential role in managing various diseases.